Jawapan

2015-08-05T20:49:27+08:00
1.
q=-2p+5
p=2q
q=-2p+5
p=2(-2p+5)
q=-2p+5
p=2(-2p)+2(5)
q=-2p+5
p=-4p+2(5)
q=-2p+5
p=-40+10
q=-2p+5
p+4p=10
q=−2p+5 
5p=10
q=−2p+5 
p=2
q=−2(2)+5 
p=2
q=−4+5 
p=2
q=1 
p=2

2.
x=2y+8 
2x−5y=19
x=2y+8 
2(2y+8)−5y=19
x=2y+8 
4y+16−5y=19
x=2y+8 
−y+16=19
x=2y+8 
−y=−16+19
x=2y+8 
−y=3
x=2y+8 
y=−3
x=2(−3)+8 
y=−3
x=−6+8 
y=−3
x=2 
y=−3

3.
2k=−3h+8 
5k−2h=−18
k=−3h/2+4 
5k−2h=−18
k=−3h/2+4 
5(−3h/2+4)−2h=−18
k=−3h/2+4 
15h/2+20−2h=−18
k=−3h/2+4 
−(15h)−2h⋅2/2+20=−18
k=−3h/2+4 
19h/2+20=−18
k=−3h/2+4 
19h/2=−20−18
k=−3h/2+4 
19h/2=−38
k=−3h/2+4 
−19h=−38⋅(2)
k=−3h/2+4 
−19h=−76
k=−3h/2+4 
h=4
k=−3(4)/2+4 
h=4
k=−6+4 
h=4
k=−2 
h=4

4.
2g+3h=7 
g=2h+7
2(2h+7)+3h=7 
g=2h+7
4h+14+3h=7 
g=2h+7
7h+14=7 
g=2h+7
7h=−14+7 
g=2h+7
7h=−7 
g=2h+7
h=−1 
g=2h+7
h=−1 
g=2(−1)+7
h=−1 
g=−2+7
h=−1 
g=5
2 5 2